Secondhand smoke exposure during pregnancy and its effect on birth outcomes: Evidence from a retrospective cohort study in a tertiary care hospital in Bengaluru - Priya Mary Prince; Marciya Umman; Farah Naaz Fathima; Avita Rose Johnson (Wolters Kluwer Medknow Publications, 2021)
Context: The effect of maternal smoking on birth outcomes is well-established, but the effect of maternal secondhand smoke (SHS) exposure is less clear, especially among Indian women. Aim: To evaluate the effect of SHS exposure during pregnancy on birth outcomes such as gestational age at birth, neonatal anthropometry, and Apgar score. Setting and Design: Retrospective cohort study at a tertiary hospital in Bengaluru. Methods: 208 postnatal mothers: 104 each in "exposed" and "nonexposed" group, based on the history of SHS exposure during pregnancy. Sociodemographic and obstetric details were obtained by interview schedule and birth outcomes were obtained from patient charts. Statistical Analysis: Association of SHS exposure with birth outcomes was analyzed using inferential statistics such as Chi-square, t-test, and Mann-Whitney U-test, whereas the strength of association was expressed as relative risk with 95% confidence intervals. P < 0.05 was considered statistically significant. Results: SHS exposed and nonexposed groups were comparable with regard to potentially confounding socioeconomic and obstetric covariates. Babies born to SHS-exposed mothers had significantly lower mean birth weight, mean birth length, and mean birth head circumference by 172.5 g (P = 0.027), 1.6 cm (P = 0.001), and 1.1 cm (P = 0.001), respectively. Conclusion: Mothers exposed to SHS during pregnancy were twice likely to deliver low birth weight babies (relative risk [RR] = 1.9 [1.0-3.6], P = 0.02) and babies of low birth length (RR = 2.64 [1.4-4.6], P = 0.001) than unexposed mothers. With a significant risk of adverse birth outcomes found among mothers exposed to SHS during pregnancy, it is important that a "no tobacco smoke" environment at home should be recommended for pregnant women and their families.